2022
DOI: 10.26719/emhj.22.077
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gender gap in surgical specialties among Lebanese medical personnel: the need for involvement of women in surgery

Abstract: Background: Little is known about gender disparity in the surgery specialty in Lebanon. Aims: To assess the status of female surgeons and possible gender gaps in surgery specialty in Lebanon. Methods: The study was conducted in May 2021. Data were retrieved from the Lebanese Order of Physicians website, indicating the number of physicians in the different specialties, their gender, hospitals, and locations. The c2 test of homogeneity was used to establish whether the gender distribution was equal. Results: Wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…the increased female representation in medicine, women remain under-represented in surgical specialties around the world. [3][4][5] For instance, previous research showed that in 2019, the proportion of active US female surgeons was 22% in general surgery, 8% in thoracic surgery, and 6% in orthopedic surgery, 6 with only 26 general surgery chairwomen across the United States and Canada in 2023. 7 Neurosurgery is no exception to this.…”
mentioning
confidence: 99%
“…the increased female representation in medicine, women remain under-represented in surgical specialties around the world. [3][4][5] For instance, previous research showed that in 2019, the proportion of active US female surgeons was 22% in general surgery, 8% in thoracic surgery, and 6% in orthopedic surgery, 6 with only 26 general surgery chairwomen across the United States and Canada in 2023. 7 Neurosurgery is no exception to this.…”
mentioning
confidence: 99%